2007
DOI: 10.1038/sj.leu.2405062
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of thalidomide- and lenalidomide-associated thrombosis in myeloma

Abstract: The incidence of venous thromboembolism (VTE) is more than 1 per thousand annually in the general population and increases further in cancer patients. The risk of VTE is higher in multiple myeloma (MM) patients who receive thalidomide or lenalidomide, especially in combination with dexamethasone or chemotherapy. Various VTE prophylaxis strategies, such as low-molecular-weight heparin (LMWH), warfarin or aspirin, have been investigated in small, uncontrolled clinical studies. This manuscript summarizes the avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
608
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 768 publications
(641 citation statements)
references
References 102 publications
(120 reference statements)
11
608
1
9
Order By: Relevance
“…The International Myeloma Working group and ASCO recommend prophylaxis with either aspirin or LMWH for lower risk patients, and LMWH for higher risk patients receiving thalidomide or lenalidomide. 47,61 Hospitalized patients Based on randomized clinical trials of thromboprophylaxis in medically ill hospitalized patients, 62,63 and a meta-analysis that demonstrated 40% lower rates of VTE with pharmacologic prophylaxis versus placebo, 64 the current ACCP 52 and ASCO guidelines 47 strongly recommend thromboprophylaxis in hospitalized medically ill and cancer patients, respectively. However, trials of thromboprophylaxis did not include HSCT patients who are not specifically included in these recommendations.…”
Section: Multiple Myelomamentioning
confidence: 99%
“…The International Myeloma Working group and ASCO recommend prophylaxis with either aspirin or LMWH for lower risk patients, and LMWH for higher risk patients receiving thalidomide or lenalidomide. 47,61 Hospitalized patients Based on randomized clinical trials of thromboprophylaxis in medically ill hospitalized patients, 62,63 and a meta-analysis that demonstrated 40% lower rates of VTE with pharmacologic prophylaxis versus placebo, 64 the current ACCP 52 and ASCO guidelines 47 strongly recommend thromboprophylaxis in hospitalized medically ill and cancer patients, respectively. However, trials of thromboprophylaxis did not include HSCT patients who are not specifically included in these recommendations.…”
Section: Multiple Myelomamentioning
confidence: 99%
“…All patients treated with Rd require antithrombosis prophylaxis. Aspirin is adequate for most patients, but in patients who are at higher risk of thrombosis, either low-molecular weight heparin or coumadin is needed [53][54][55].…”
Section: Risk-adapted Therapymentioning
confidence: 99%
“…Taking all this into account, one should consider preventive measures to reduce thrombotic complications in multiple myeloma patients receiving chemotherapy, especially when combined with thalidomide. Currently, there are only recommendations on thromboprophylaxis for multiple myeloma patients who are treated with thalidomide-or lenalidomide-containing regimens [10]. In these patients, thromboprophylaxis with low molecular weight heparin (LMWH) is effective in reducing thrombotic complications [9].…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, thromboprophylaxis with low molecular weight heparin (LMWH) is effective in reducing thrombotic complications [9]. Several studies have shown that aspirin is also effective in reducing thrombotic events [10]. In a recent prospective, multicenter study, low-dose warfarin, LMWH and aspirin were compared in patients treated for newly diagnosed multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%